Cervical Intraepithelial Neoplasia Rates in British Columbia Women: A Population-Level Data Linkage Evaluation of the School-Based HPV Immunization Program. (23rd August 2019) - Racey, C Sarai; Albert, Arianne; Donken, Robine; Smith, Laurie; Spinelli, John J; Pedersen, Heather; de Bruin, Pamela; Masaro, Cindy; Mitchell-Foster, Sheona; Sadarangani, Manish; Dawar, Meena; Krajden, Mel; et al.
Abstract: Background: To understand real-world human papillomavirus (HPV) vaccine impact, continuous evaluation using population-based data is critical. We evaluated the early impact of the school-based HPV immunization program on cervical dysplasia in women in British Columbia, Canada. Methods: Data linkage was performed using records from provincial cervical screening and immunization registries. Precancerous outcomes were compared between unvaccinated and HPV-vaccinated women born 1994–2005. Incidence rate, relative rate (RR), and vaccine effectiveness (VE), using unadjusted and adjusted Poisson regression of cytology (HSIL) and histopathology (CIN2, CIN3, and CIN2+) outcomes, were compared across vaccination status groups. Results: Women who received a complete series of vaccine on schedule between age 9 and 14 years had an adjusted RR = 0.42 (95% confidence interval [CI], 0.31–0.57) for CIN2+ over 7 years of follow-up compared to unvaccinated women, resulting in a VE of 57.9% (95% CI, 43.2%–69.0%). Adjusted RR for HSIL was 0.53 (95% CI, .43–.64), resulting in a VE of 47.1% (95% CI, 35.6%–56.7%). Conclusion: Women vaccinated against HPV have a lower incidence of cervical dysplasia compared to unvaccinated women. Immunization between 9 and 14 years of age should be encouraged. Continued program evaluation is important for measuring long-term population impact. Abstract : A data linkage of the cervix screening program registry to the immunization registry in British Columbia showed that women vaccinated against HPV have a lower incidence of cervical dysplasia compared to unvaccinated women.